Traductor scriptor : the old Greek translation of Exodus 1-14 as scribal activity - Screnock, John. (Vetus Testamentum, Supplements, 2017)
In Traductor Scriptor , John Screnock situates the Old Greek translation of the Hebrew Bible within the broader scribal culture of the ancient world. Building on current methods in Septuagint studies and textual criticism, Screnock engages the evidence from Qumran, the Samaritan Pentateuch, and the Old Greek to argue that the phenomena of translation and transmission are fundamentally similar. Traductor Scriptor presents a unique approach to the use of the Old Greek for textual criticism of the Hebrew Bible, based on new theoretical considerations and an in-depth analysis of text-critical data in the Old Greek translation and Hebrew manuscripts of Exodus 1-14.